The Influence of Exercise Training on Quality of Life and Psychosocial Functioning in Children with Congenital Heart Disease:A Review of Intervention Studies - Karolijn Dulfer; Willem A. Helbing; Elisabeth M. W. J. Utens (MDPI AG, 2017)
Children and adolescents operated upon for congenital heart disease may show reduced exercise capacity and physical activity, associated with lowered quality of life. This review presents intervention studies on the influence of an exercise program on quality of life and psychosocial functioning in children with severe congenital heart disease. Participation in an exercise program among young people with complex congenital heart disease seemed to have positive effects on quality of life and passive leisure time spent. However, more effects of the exercise programs may have been expected. For future research it is important to critically evaluate the content of the exercise programs.